Effects of phosphate chemicals treatments on auto battery waste contaminated soil in Nigeria (2009)
Auto battery waste contaminated site poses potential threats to the environment and biological life through lead toxicity, thus making remediation imperative. The possibility of using phosphate chemicals to reclaim a grossly lead-contaminated site was explored. The study site was an abandoned lead-acid battery waste dumpsite in Nigeria. Phosphate chemicals were applied at 5 and 10% phosphorus levels to the contaminated soil collected from the site in incubation experiments. The air-dried sub-samples of the incubated soils were analyzed for pH, P, bioavailable Pb and TCLP- extractable Pb. Results showed that 99.5% of the applied phosphorus was removed by the end of the first week of incubation. Incubation time showed less effect on Pb immobilization. A 10% phosphorus application resulted in reductions of water soluble Pb between 77.8% and 86.4% thus eliminating to a reasonable extent, the hazard to living things and the environment. TCLP extractable Pb was reduced from 50.2 mg/L in untreated soil to below the acceptable value of 5.0 mg/L. An application of 10% CHP produced overall effectiveness in the reduction of bioavailable Pb, TCLP-extractable soil Pb. This treatment also had little effect on soil acidification and resulted in the least residual P. Results therefore indicated that phosphorus can be used as potential chemical remediation for cleanup of battery waste contaminated soils.